2020
DOI: 10.1038/s41586-020-2016-3
|View full text |Cite
|
Sign up to set email alerts
|

Strain-hardening and suppression of shear-banding in rejuvenated bulk metallic glass

Abstract: Strain-hardening (the increase of flow stress with plastic strain) is the most important phenomenon in the mechanical behaviour of engineering alloys because it ensures that flow is delocalized, enhances tensile ductility and inhibits catastrophic mechanical failure 1,2. Metallic glasses (MGs) lack the crystallinity of conventional engineering alloys, and some of their properties-such as higher yield stress and elastic strain limit 3-are greatly improved relative to their crystalline counterparts. MGs can have… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
82
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 243 publications
(92 citation statements)
references
References 41 publications
10
82
0
Order By: Relevance
“…3b). The maximum absolute value of ΔH rel of 0.81 kJ/mol is comparable to previously reported sub T g mechanical rejuvenation techniques, including high pressure torsion and notched triaxial strain, 16,20,42 and is among the highest reported changes in enthalpy of relaxation when compared to the reference sample.…”
Section: Resultssupporting
confidence: 83%
See 1 more Smart Citation
“…3b). The maximum absolute value of ΔH rel of 0.81 kJ/mol is comparable to previously reported sub T g mechanical rejuvenation techniques, including high pressure torsion and notched triaxial strain, 16,20,42 and is among the highest reported changes in enthalpy of relaxation when compared to the reference sample.…”
Section: Resultssupporting
confidence: 83%
“…[7][8][9] Recognizing such limitations in realizing a ductile state under BMG forming conditions has led to the development of processing strategies to enhance ductility after the glass has already been formed. Such strategies are based on mechanical means, 10 and include irradiation, [11][12][13][14][15] static loading, [16][17][18][19][20] cyclic loading, 21 shot peening, 22 rolling, 23 twin roll casting, 24 thermal cycling, [25][26][27][28] and severe plastic deformation. 29,30 A summary of previous results can be found in the supplementary material in table 1.…”
Section: Introductionmentioning
confidence: 99%
“…The SARS epidemic in 2003 as well the current COVID-19 pandemic, caused by two members of the Coronavirus family SARS-CoV and SARS-CoV-2, respectively, have directed attention towards the interaction of Coronaviruses with the RAS. mACE2 serves as a binding site for SARS-CoV [64,65] and SARS-CoV-2 [66,67], mediating the entry of the virus into the host cell. A mutation in the receptor-binding domain of the SARS-CoV-2 spike protein S compared to SARS-CoV is responsible for a higher affinity of SARS-CoV-2 to ACE2 [67].…”
Section: Interactions With Infectious Agentsmentioning
confidence: 99%
“…Bulk metallic glasses (BMGs) are materials with excellent performance and mechanical properties, such as high yield strength [ 1 ], high toughness [ 2 ], high hardness [ 3 ] and exceptional “damage tolerance” [ 4 , 5 ]. However, the nonuniform deformation caused by the highly localized deformation at room temperature directly causes its brittleness [ 6 , 7 ], which has become the bottleneck for the widespread application of BMGs.…”
Section: Introductionmentioning
confidence: 99%
“…Through plastic deformation under triaxial compression at room temperature, Y. Li and A.L. Greer [ 4 ] rejuvenated BMGs samples and found that the rejuvenated amorphous material showed excellent plastic deformation ability. However, elastic loading [ 17 ], ion radiation [ 18 ], thermal cycling [ 19 , 20 ], and plastic deformation [ 21 ] methods require a substantial amount of time to rejuvenate the BMGs, and during this time, a relaxation effect inevitably occurs, weakening the rejuvenation effect.…”
Section: Introductionmentioning
confidence: 99%